Electric-car surfer. - Voelcker, J. (IEEE spectrum)
An unlikely automotive engineer oversees all the electricity at a revolutionary vehicle start-up. Even after working on the thing for years, Brian Gallagher can't forget how astounding the sight of an Aptera in the wild can be. When one came barreling toward him and his wife recently, he says, he yelled just as loudly as she did. "It was shocking."